Radiowa manipulacja słuchaczem za pomocą materiału muzycznego - Massaka, Iwona (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2006)
The analysis of the material broadcast by radio stations leads the Author to conclude that at present radio aspires to become one of the main providers of entertainment. The advertising slogans, statements of radio anchorpersons, news, songs or jingles make radio broadcasts something like a musical. This musical content remarkably contributes to the atmosphere of lightheartedness and optimism. Music is fragmented to the same degree as the news or announcements, and the listener is usually forced to listen to only a fragment of a speech or song. The recordings are not run to the very last sounds as when one approaches its ending the beginning of another one overlaps it immediately. Mixes of different songs are also played, including several bars of each, which is reminiscent of a video-clip for the ears.
Manipulating a Radio Listener by Means of Music Broadcasting